ELEMENTARY TEACHERS’ PERCEPTIONS AS TO WHAT CONTRIBUTES TO STUDENT ACHIEVEMENT - Sickenger, Heather (Acta Scientiae et Intellectus, 2024)
Student achievement can be described in various ways. Some might define student achievement as standardized test scores or grades from teachers. Others might say student achievement is being engaged and motivated in class lessons and activities. Still others might say it is modifying one’s challenging behavior to accomplish tasks, and make better choices. Nonetheless, student achievement should be highlighted in all aspects of making a change for positive lifelong outcomes. Today’s classrooms are so different from classrooms of the past. Past research states that teachers are one of the most influential reasons for student achievement. However, in today’s classrooms, teachers’ perceptions of what contributes to student achievement are not being addressed. This study is designed to give elementary teachers a platform to share their perceptions of what contributes to student achievement. Elementary teachers from the largest public school district in New Mexico will be invited to participate. The elementary teachers within the district will receive a link to a web-based survey from their principals. The data from the survey will collect new data perceptions and current representations of what elementary teachers think and believe contributes to student achievement.